Efficacy of Mechanical Thrombectomy in Acute Ischemic Stroke: Predictors of Functional Recovery and Mortality - Sattar, Warda; Khan, Amanullah; AI, Aburabee; Rani, Reeta; Ihsan, Nida; Ahmed, Syed Naseer; Mehtab, Ghazal; Aziz, Abdul; Mian Ayaz Ul Haq (Indus Journal of Bioscience Research, 2024)
Introduction: Acute ischemic stroke (AIS) remains one of the leading causes of morbidity and mortality globally, with an immense burden on healthcare systems and families. Objective: The basic aim of the study is to find the efficacy of mechanical thrombectomy in acute ischemic stroke as a predictor of functional recovery and mortality. Methodology: The study conducted at Hayatabad Medical Complex in Peshawar analyzed 354 patients who underwent mechanical thrombectomy (MT) from June 2022 to May 2023. Exclusions included those with hemorrhagic stroke, incomplete records, and those who did not undergo MT. Data from patients’ medical records included demographics, clinical history, concomitant disorders, radiological data, and therapeutic information. Stent retrievers and aspiration devices were used in MT, based on operator preference and hospital guidelines. Results: The median baseline NIHSS score was 15, indicating moderate to severe stroke severity. A high prevalence of comorbidities was observed, including hypertension (69%), diabetes (31%), and atrial fibrillation (28%). The study found that at 90 days post-procedure, 43% of patients experienced favorable functional recovery, while the mortality rate was 22%. Patients with a door-to-puncture time of 60 minutes or less had a higher recovery rate (48%), emphasizing the importance of timely intervention. Furthermore, successful revascularization (TICI 2b-3) was associated with significantly better recovery outcomes (50%) and a lower mortality rate (17%) compared to incomplete revascularization (TICI < 2b), where recovery was notably lower (20%) and mortality more than doubled (37%). Conclusion: Mechanical thrombectomy significantly improves functional recovery in acute ischemic stroke patients, especially when performed promptly and with successful revascularization tract.